Kenya's South Africans and the Politics of Decolonization - (:unkn) unknown (My University, 2020)
This article examines the political impact of decolonization upon the South African community in Kenya in 1963. It stresses that the end of British rule in Kenya had different implications for different groups of South Africans in Kenya. The community has been broadly delineated into three groups. The first group is the Afrikaner farmers’ community in Kenya – a numerically small but economically strategic section of the white community which produced nearly 70 per cent of the country's wheat. The second includes those working for firms and with business interests in Nairobi, and the third includes those employed in the service of the crown. The three state actors, Britain, South Africa, and Kenya, consciously used this opportunity to define and reinforce their state ideology in opposition to one other in an intra-African theatre. South Africa attempted to establish itself as the preferred white man's dominion in Africa, while Kenya used it to entrench its anti-apartheid position whilst taking the stand that Afrikaners who renounced apartheid could stay on in Kenya. Britain prioritized the interests and demands of the British settlers in Kenya as well as its new comprehensive strategic alliance with the new Kenyan government, and made concessions to Afrikaners within this framework.
Keywords: African Research